Minority Women and Austerity Survival and Resistance in France and Britain - Bassel, Leah (2017)
In the first book of its kind, Bassel and Emejulu explore minority women's experiences of and resistances to austerity measures in France and Britain. Minority women are often portrayed as passive victims. However, Minority women and austerity demonstrates how they use their race, class, gender and legal status as a resource for collective action in the face of the neoliberal colonisation of non-governmental organisations, the failures of left-wing politics and the patronising initiatives of policy-makers. Using in-depth case studies, this book explores the changing relations between the state, the market and civil society which create opportunities and dilemmas for minority women activists. Through an intersectional 'politics of survival' these women seek to subvert the dominant narratives of 'crisis' and 'activism'.